Interoperability of telemonitoring data in digital health solutions: a scoping review - Martins, Diogo; Lewerenz, Simon; Carmo, Anderson; Martins, Henrique (Frontiers in Digital Health, 2025)
ObjectivesThis scoping review explores the existing literature on the interoperability of telemonitoring systems in cross-border healthcare settings. It focuses on identifying technical standards, enablers, and barriers to effective telemonitoring data exchange across healthcare systems and geographies.MethodsA systematic search was conducted across databases (MEDLINE, PubMed, ISI Web of Knowledge, DBLP, and Scopus) from January 2000 to May 2023, using keywords such as “telemonitoring”, “interoperability”, “technical standards”, and “cross-border data exchange”. Eligibility criteria included peer-reviewed studies examining the interoperability of telemonitoring systems across healthcare providers and cross-border settings. A total of 861 studies were identified, and 25 met the inclusion criteria.ResultsThe review identified diverse technical standards, including HL7 FHIR, ISO/IEEE 11073, and IHE profiles, used in telemonitoring systems. However, significant gaps were found in the literature regarding the operational challenges of telemonitoring systems, particularly in cross-border contexts. Many studies focused on technical aspects, with fewer addressing organizational and legal issues. Data transport types, such as Bluetooth and REST APIs, were mentioned, but no common standard for data exchange between devices was identified.DiscussionThe findings highlight the need for further research on the deployment of telemonitoring systems, particularly in cross-border contexts. The lack of harmonization in technical standards poses a barrier to achieving seamless interoperability. The review calls for the development of a robust framework to support telemonitoring integration across healthcare systems.ConclusionsWhile telemonitoring shows promise in improving healthcare delivery, significant interoperability challenges remain. Developing common standards at the European level is essential to enhance cross-border telemonitoring services and patient care.